Enhancing ASEAN's connectivity - Basu Das, Sanchita (Institute of Southeast Asian Studies, 2013)
ASEAN has a goal to create an economic community by 2015. To achieve the goal, connectivity among the member states needs to be given due importance. In 2010, ASEAN adopted the Master Plan on ASEAN Connectivity (MPAC), which looked at physical, institutional and people-to-people connectivity. It pinned down fifteen priority projects which can potentially transform the ASEAN region, providing the conditions for a single market and production base. But MPAC is an expensive initiative, and funding remains a major challenge. The private sector needs to be actively involved as a number of infrastructure projects identified in the MPAC are lacking substantial investment. This book looks at the current state of ASEAN's physical connectivity and challenges in building better infrastructure. It contains a collection of papers that discuss specific issues pertaining to each kind of physical connectivity transportation infrastructure, telecom connectivity, ICT and energy infrastructure. The book concludes with the steps needed to be taken for implementation of the various plans, and policy recommendations.